1976
DOI: 10.7326/0003-4819-85-1-39
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Staphylococcal Abscesses Associated with Defective Neutrophil Chemotaxis and Allergic Rhinitis

Abstract: Four patients with recurrent staphylococcal furonculosis and deep abscess formation were evaluated to determine if a defect in the host defense mechanism could account for the unusual incidence of infection. Each also suffered repeated allergic rhinitis, often preceding the onset of infection. A marked defect in neutrophil granulocyte chemotaxis occurred when the patients were symptomatic with rhinitis and abscess formation. Their mean chemotactic index (+/- SD) was 16 +/- 6, while that of 25 control subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

1979
1979
2002
2002

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(7 citation statements)
references
References 13 publications
2
5
0
Order By: Relevance
“…The defect was modest in degree which could explain the absence of associated recurrent infections in 4 of the 5 patients studied. These findings are similar to that reported by Hill et al [1] in allergic patients without staphylococ cal infections. Only 1 of our patients suffered from minor infections that occurred yearly in spring.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…The defect was modest in degree which could explain the absence of associated recurrent infections in 4 of the 5 patients studied. These findings are similar to that reported by Hill et al [1] in allergic patients without staphylococ cal infections. Only 1 of our patients suffered from minor infections that occurred yearly in spring.…”
Section: Discussionsupporting
confidence: 82%
“…The association of allergic rhinitis, defective gran ulocyte chemotaxis, and recurrent staphylococcal skin abscesses has been reported [1], The mechanism of the granulocyte dysfunction in these patients is not known, but one possibility is that the IgE-mediated histamine release may be responsible. This is based upon in vitro studies showing binding of histamine to leukocytes and their displacement with antihista mines [2], induction of increased intracellular cyclic AMP and diminished chemotactic responses in gran ulocytes incubated with histamine, and the preven tion of these effects in granulocytes protected with burimamide, an histamine Hs-receptor blocker [3].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with atopic disease and recurrent staphylococcal furunculosis may have transiently abnormal granulocyte locomotion. Hill et al [34] found depressed chemotaxis during allergic symptomatology but normal granulocyte chemotactic responsiveness when staphylococcal furuncles were being treated.…”
Section: Patients With Increased Serum Ige Without Serious Infectionsmentioning
confidence: 99%
“…Low levels of secretory IgA or of the second component of com plement and defects of the alternative pathway of complement are much more frequent among atopic children than in the general population [Soothill and Har vey, 1976;Siccardi et al, 1980Siccardi et al, , 1981, Moreover, defective neutrophil chemotaxis has been described in patients with marked allergic diseases and recurrent infections [Hill et al, 1976]. Recently, quantitative and qualitative changes in T cells have been described in atopic derma titis and respiratory allergy with increased IgE levels.…”
Section: Introductionmentioning
confidence: 99%